Verity Fairy AND Rapunzel - Wakeman, Caroline; Zhing, Amy (New York : DK Publishing, 2021)
In this captivating interpretation of a classic fairytale, children can rediscover the much-loved story of Rapunzel while exploring the Magic Kingdom of the fairies--a place where all of the classic fairytales coexist and intertwine. In this retelling of Rapunzel, youngsters can follow Verity and her fairy friends in the Fairy-tale Kingdom and see how they help good prevail over evil, making sure everyone lives happily ever after. Verity means truth, and that is exactly what she does, she tells the truth, ALL the time, and it often gets her into a lot of trouble!
Keywords: Fairies -- Juvenile fiction; Fairy tales